1971
DOI: 10.1037/h0030724
|View full text |Cite
|
Sign up to set email alerts
|

Manifest anxiety as a contributing factor in religious conversion.

Abstract: Glen D, Baskett Educational Testing ServiceThis study investigated the relationship between manifest anxiety and religious conversion. Three groups of residents (N = 20 each) in a predominantly Protestant taNn were identified by the community's two ministers: those haVing had a sudden religious conversion experience, those having had a more gradual religious development, and those who were not religious at all, The Taylor Manifest Anxiety Scale was administered to the members of each group" The gradual religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Overall conclusions about anxiety and religiosity are dif cult to draw from the literature in part because identi ed relationships have been between speci c dimensions of religious experience and speci c types of anxiety. Differences in anxiety levels based on denominational status (Hertsgaard & Light, 1984;Levendusky & Belfer, 1988;Spellman et al, 1971) suggested that elements of religiosity which may impact anxiety were likely to be comparatively complex constellations of both content of belief and culture of the religious reference group. In an effort to bring greater clarity to this area of inquiry, the present study has used a principal components analysis to collapse several dimensions of religiosity into more interpretable supervariables, so that it may be possible to identify relationships anxiety may have not just with religiosity, but with de nable ways of being religious.The components of religiosity chosen were selected to tap aspects of the content of belief and the nature of relationships the believer experiences with both a Deity and compatriots in the reference group, such as level of scriptural literalism, acceptance of group standards, level of commitment and approaches to prayer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall conclusions about anxiety and religiosity are dif cult to draw from the literature in part because identi ed relationships have been between speci c dimensions of religious experience and speci c types of anxiety. Differences in anxiety levels based on denominational status (Hertsgaard & Light, 1984;Levendusky & Belfer, 1988;Spellman et al, 1971) suggested that elements of religiosity which may impact anxiety were likely to be comparatively complex constellations of both content of belief and culture of the religious reference group. In an effort to bring greater clarity to this area of inquiry, the present study has used a principal components analysis to collapse several dimensions of religiosity into more interpretable supervariables, so that it may be possible to identify relationships anxiety may have not just with religiosity, but with de nable ways of being religious.The components of religiosity chosen were selected to tap aspects of the content of belief and the nature of relationships the believer experiences with both a Deity and compatriots in the reference group, such as level of scriptural literalism, acceptance of group standards, level of commitment and approaches to prayer.…”
Section: Discussionmentioning
confidence: 98%
“…Hertsgaard and Light (1984) found similar differences in anxiety levels based on denominational af liation. Also considering denominational status, individuals who had experienced a religious conversion evidenced higher levels of anxiety than those who evidenced more gradual religious growth or those who were not religious (Spellman et al, 1971). Wilson and Miller (1968) found that those who reported more participation in religious practices also reported higher levels of anxiety.Two studies of Asian participants also support the hypothesis that traditional religious beliefs are correlated with higher levels of anxiety (Gupta, 1983;Hassan & Khalique, 1981).…”
Section: Religiosity and Anxietymentioning
confidence: 97%
“…For example, Wilson and Miller (1968) found that nonreligious undergraduates tended to report less fearfulness and anxiety. Spellman, Baskett, and Byrne (1971) found that religious converts tended to report higher anxiety than nonreligious individuals or regular attendees. More recently, however, Butler (2000) found no relationship between right‐wing authoritarianism (RWA) scores and scores on the Positive and Negative Affect Schedule items for scared, nervous, and afraid.…”
Section: Religious Fundamentalism and Prejudicementioning
confidence: 95%
“…While recent research supports an association between religious/spiritual commitment and lower anxiety, some research has shown a relationship between religiousness/spirituality and higher anxiety (Spellman, Baskett & Byrne, 1971;Wilson & Miller, 1968). Other studies have shown no relationship (Heintzelman & Fehr, 1976).…”
mentioning
confidence: 96%